ナンキョクイキ ニオケル ゴウセイ カイコウ レーダー (SAR) ガゾウ ノ セッピョウ ケンキュウ ヘノ オウヨウ - 高橋, 晃; タカハシ, アキラ; 藤井, 理行; フジイ, ヨシユキ; 長, 幸平; チョウ, コウヘイ; 西尾, 文彦; ニシオ, フミヒコ; 古川, 晶雄; フルカワ, テルオ; 渡辺, 興亜; ワタナベ, オキツグ; et al. (1995)
P(論文) 昭和基地で1991年から1993年までに受信された, ERS-1,JERS-1のSAR画像解析について述べる。解析は, リュツォ・ホルム湾からやまと, ベルジカ山脈を含む領域を対象領域に選んで行った。海氷域では, 表面の滑らかな裸氷域の後方散乱は非常に弱く, 雪に覆われた一年氷, 多年氷, 氷山の識別もMOS-1/MESSR画像と比べて容易に行えることが分かった。夏季と冬季のERS-1画像の比較からは, 冬季には海氷の成長に関連すると思われる後方散乱の増加が認められた。氷床域では, 沿岸から内陸にかけて, 後方散乱に著しい変化が見られた。氷床縁辺部の裸氷域では後方散乱が非常に弱く, 積雪中の融解水が再凍結を起こす領域の後方散乱は強いことが分かった。また, 乾雪線付近の平坦な雪面域では後方散乱が非常に弱いことが分かった。ヌナタク周辺では氷床の基盤地形を反映した表面起伏と表面状態に起因すると思われる斑点状の散乱が認められた。 Antarctic sea ice and ice sheet were studied using the ERS-1 and JERS-1 SAR images received at Syowa Station in 1991-1993. Analysis was mainly done for sea ice in Lutzow-Holm Bay, ice streams flowing into the bay, ice sheet near the coast and inland nunataks. Back scattering coefficient of the SAR images differs clearly between first-year and multi-year sea ice covered with snow which are difficult to be distinguished in the MOS-1/MESSR images. Weak scattering is confirmed in bare sea ice because of the smooth surface and appears in summer comparing with that in winter. The back scattering differs clearly place to place in ice sheet weak in bear ice along the coast very week in the smooth dry snow area and scattered near nunataks. departmental bulletin paper